KEPEMIMPINAN DI MADRASAH (Kajian atas Kepemimpinan Transformasional dalam Perpsketif Al-Qur’an dan Literatur Kesarjanaan Kontemporer) - Mustofa Fahmi (STIT AL-AMIN KREO TANGERANG, 2022)
This study discusses transformational leadership in madrasas from the perspective of the Qur'an and contemporary leadership theories. Transformational leadership in madrasas is a leadership style that encourages, fosters, directs, and motivates subordinates to excel. Through the scholarly approach and literature, several stages can be formulated in implementing it in madrasas, including; a) formulate a vision; b) develop madrasah culture; c) create synergy; d) empowering subordinates; e) creating change; f) develop the professionalism of subordinates; g) refers to the social system; h) make madrasas as learning organizations. Analyzing the findings which later became the conclusions in this study were obtained using the library research method or literature studies with the main source of the Qur'an and several literature studies related to contemporary leadership styles. Transformational leadership which is formulated through several stages contributes greatly to creating a leadership culture that is not only trustworthy, but also an inspiration for madrasa residents, especially the head of the madrasa to always make changes and innovations. Although this leadership style is found in contemporary scholarly literature, it turns out that some of these stages also have a strong theological basis and foundation from the Qur'an. Madrasah leaders and residents both realize the importance of the involvement of all parties in efforts to improve the quality of madrasas. A leadership perspective that places the Qur'an as the theological foundation to encourage and motivate subordinates to excel.